PENGGUNAAN MEDIA SOSIAL INSTAGRAM DAN BODY IMAGE TERHADAP KEPERCAYAAN DIRI SISWA - Faiqoh Nurul Arista; Eko Harianto; Patria Jati Kusuma (PT. Hasba Edukasi Mandiri, 2025)
This study examines the effect of Instagram social media use and body image on students’ self-confidence at SMA Negeri 9 Purworejo. In the digital era, social media platforms such as Instagram have become a dominant space for adolescents to interact, present themselves, and seek social validation. Excessive exposure to idealized images can shape body image and influence self-confidence. Using a quantitative correlational design, the research involved 170 students selected through purposive sampling. Data were collected via Likert-scale questionnaires measuring Instagram use, body image, and self-confidence. Multiple linear regression analysis revealed that Instagram use and body image simultaneously have a significant positive effect on self-confidence. These findings indicate that healthy Instagram use and a positive body image contribute to greater self-confidence among students, highlighting the importance of social media literacy and self-acceptance in adolescence.